Heterologous Expression of the Cotton NBS-LRR Gene GbaNA1 Enhances Verticillium Wilt Resistance in Arabidopsis - Li, Nan-Yang; Zhou, Lei; Zhang, Dan-Dan; Klosterman, Steven J.; Li, Ting-Gang; Gui, Yue-Jing; Kong, Zhi-Qiang; Ma, Xue-Feng; Short, Dylan P. G.; Zhang, Wen-Qi; Li, Jun-Jiao; Subbarao, Krishna V.; et al. (Frontiers in Plant Science, 2018)
Verticillium wilt caused by Verticillium dahliae results in severe losses in cotton, and is economically the most destructive disease of this crop. Improving genetic resistance is the cleanest and least expensive option to manage Verticillium wilt. Previously, we identified the island cotton NBS-LRR-encoding gene GbaNA1 that confers resistance to the highly virulent V. dahliae isolate Vd991. In this study, we expressed cotton GbaNA1 in the heterologous system of Arabidopsis thaliana and investigated the defense response mediated by GbaNA1 following inoculations with V. dahliae. Heterologous expression of GbaNA1 conferred Verticillium wilt resistance in A. thaliana. Moreover, overexpression of GbaNA1 enabled recovery of the resistance phenotype of A. thaliana mutants that had lost the function of GbaNA1 ortholog gene. Investigations of the defense response in A. thaliana showed that the reactive oxygen species (ROS) production and the expression of genes associated with the ethylene signaling pathway were enhanced significantly following overexpression of GbaNA1. Intriguingly, overexpression of the GbaNA1 ortholog from G. hirsutum (GhNA1) in A. thaliana did not induce the defense response of ROS production due to the premature termination of GhNA1, which lacks the encoded NB-ARC and LRR motifs. GbaNA1 therefore confers Verticillium wilt resistance in A. thaliana by the activation of ROS production and ethylene signaling. These results demonstrate the functional conservation of the NBS-LRR-encoding GbaNA1 in a heterologous system, and the mechanism of this resistance, both of which may prove valuable in incorporating GbaNA1-mediated resistance into other plant species.